Association between body composition and the risk of mortality in the obese population in the United States - Lee, Heeso; Chung, Hye Soo; Kim, Yoon Jung; Choi, Min Kyu; Roh, Yong Kyun; Yu, Jae Myung; Oh, Chang-Myung; Kim, Joon; Moon, Shinje (Frontiers in Endocrinology, 2023)
Background Recent studies have presented the concept of the obesity paradox, suggesting that individuals with obesity have a lower risk of death than those without obesity. This paradox may arise because body mass index (BMI) alone is insufficient to understand body composition accurately. This study investigated the relationship between fat and muscle mass and the risk of mortality in individuals with overweight/obesity. Methods We used data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2006 and 2011 to 2018, which were linked to mortality information obtained from the National Death Index. Multiple Cox regression analyses were performed to estimate mortality risk. Subgroup analysis was conducted using propensity score-matched (PSM) data for age, sex, and race/ethnicity. Results This study included 16,555 participants who were overweight/obese (BMI≥25 kg/m2). An increase in appendicular skeletal muscle mass index was associated with a lower mortality risk (hazard ratio [HR]: 0.856; 95% confidence interval [CI]: 0.802–0.915). This finding was consistent with the subgroup analysis of the PSM data. Contrastingly, a high fat mass index was associated with an increased risk of mortality. Sarcopenic overweight/obesity was significantly associated with high mortality compared to obesity without sarcopenia (HR: 1.612, 95%CI: 1.328–1.957). This elevated risk was significant in both age- and sex-based subgroups. This finding was consistent with the subgroup analysis using PSM data. Conclusion In contrast to the obesity paradox, a simple increase in BMI does not protect against mortality. Instead, low body fat and high muscle mass reduce mortality risk.